Is there a right to knowledge about our origins? - Milligan, Tony (Frontiers in Space Technologies, 2023)
Is there a right to knowledge about the origins of life and the origins of humanity? Knowledge of a sort that astrobiology may be able to supply. And a right of the sort that might be acknowledged within international declarations, agreements, and codes of conduct. A distinguishing feature of the paper is an argument strategy that draws upon pragmatic discussions of animal rights and links such a pragmatic idea of rights to interests. The background thought here is that discussions of rights in the non-human case can enrich our understanding of the rights that we should ascribe to humans as well as our understanding of what it means to ascribe a right. A right to knowledge about our origins can be supported by the classic autonomy-based approach towards rights, given that such a right would help to optimize the conditions under which autonomy is exercised. However, the case for a right to knowledge about origins strengthens when we draw upon a more interest-based approach and say that rights can also be tied to strong interests. In order to support the idea that humans have a sufficiently strong interest in the relevant kinds of knowledge, i.e., astrobiological knowledge about origins, appeal is made to the historical spread, depth and persistence of our human concern with origins, evidenced by Indigenous cosmologies and storytelling about how life began. Our history as a moral community is, in part, a history of reflection upon origins, with astrobiology functioning as a recent and productive way of engaging in such reflection.